Educação de surdos em Passo Fundo : momentos da história da escolarização - Souza, Tatiane de (2014)
This work lies in the field of studies on deafness. It aims to investigate how the movement for the right education of the deaf occurred in Passo Fundo/RS and how it reached the educational processes to which the hearing impaired were submitted in order to provide elements to the history of education of the deaf population from the city. The questions that guided the study were: What methods were used to promote the schooling ofdeaf? What was the role (s) of language (s) (Brazilian Sign Language and Portuguese) in process education of the deaf? What feelings have the hearing impaired produced during their passage through the schools where they studied? What continuities and ruptures happened in deaf education when they started regular school and were no longer attending special school? The research is justified by the need to put into question the inclusion of deaf in regular education from the official discourse represented by the Ministry of Education? MEC and the Brazilian educational legislation dealing with special education, besides demonstrating the desire of the deaf community to be recognized by their group as a linguistic minority in the educations cenario. For data collection the following resources were used: autobiographical memory of the researcher; records collected in Escola Ponte; Minute books of the Association of Parents and Friends of the Deaf and Association of the Deaf, both in the city of Passo Fundo; asemi-structured interview with former presidents of APAS and ASPF; and a semi-structured interview with students from Escola Ponte. The analysis categories - interaction, language, bilingualism - enabled to address on the importance of group and interaction: the coexistence as a fundamental element for the inclusion; sign language as a mediator in the interaction processes: the language ofdeaf; and about the school and inclusive education, teaching practice and the confrontation with different cultures